Method for ceramicizing glass using nucleation and growth density and viscosity changes
By adjusting the heating rate and temperature during the ceramicization cycle of glass ceramics, combined with the automatic viscosity control system, the problem of heat distribution control during the ceramicization process is solved, and the formation of high-strength and high transmittance glass ceramic products is achieved.
Patent Information
- Application Number
- CN202211169748.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-11-19
- Filing Date
- 2019-07-15
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2039-07-15
AI Technical Summary
The formation of high-yield glass ceramics is difficult to accurately control the heat distribution of glass products during ceramicization, especially in stacking heating equipment, which makes it difficult to obtain glass ceramic products with high strength and high transmittance.
By adjusting the heating rate and temperature based on nucleation and growth density and viscosity changes during the ceramicization cycle, the viscosity of the glass article is monitored and maintained within the target range using an automatic viscosity control system and at a density change rate of less than or equal to 0.10 (g/ Heating is finished at cm3)/min to ensure that the density of the glass product is constant to form high-quality glass ceramics.
The precise control of the heat treatment of glass products during the ceramicization process is achieved, the mechanical and optical properties of glass ceramics are improved, and the formation of glass ceramics with high strength and high transmittance is ensured.
Smart Images

Figure CN115403256B_ABST
Abstract
Description
[0001] Divisional Application Instructions
[0002] This application is a divisional application of an invention patent application with an application date of July 15, 2018, an international application number of PCT / US2019 / 041773, a national application number of 201980047936.0 after entering the Chinese national phase, and titled "Method for ceramicizing glass using nucleation and growth density and viscosity changes".
[0003] Related Applications Cross Reference
[0004] This application claims priority under 35 U.S.C. §119 to U.S. Provisional Application Serial No. 62 / 769,253 filed on November 19, 2018 and U.S. Provisional Application Serial No. 62 / 698,623 filed on July 16, 2018, the contents of which are based on this application and are incorporated herein by reference in their entirety.
[0005] background
[0006] field
[0007] The present specification generally relates to methods of ceramizing glass articles to form glass-ceramic articles, and more particularly to methods of ceramizing glass articles to form glass-ceramic articles by adjusting a ceramizing cycle based on changes in nucleation and growth density and article viscosity during the ceramizing cycle. Technical Background
[0008] There is a continuing need for high-strength glass that can be used in portable electronic devices. Several materials are currently used as housings for portable electronic devices, such as glass, zirconium oxide, plastic, metal, and glass-ceramics. The benefits of using glass-ceramics include high strength and high transmittance, which makes glass-ceramics ideal for optical displays and electromagnetic charging.
[0009] However, forming glass-ceramics can be difficult, particularly when attempting to achieve high throughput in the ceramization process. For example, forming glass-ceramics requires precise control of the thermal profile of the glass article during the ceramization process, which becomes difficult when the glass articles are stacked in a heating device such as an annealing furnace.
[0010] Overview
[0011] According to a first aspect, a method for ceramizing a glass article into a glass ceramic comprises: placing the glass article in a heating device; heating the glass article to a first holding temperature at a first predetermined heating rate; holding the glass article at the first holding temperature for a first predetermined duration, wherein during the first predetermined duration, the viscosity of the glass article is maintained within the range of ±1.0 poise of the logarithmic viscosity of the target viscosity; heating the glass article from the first holding temperature to a second holding temperature at a second predetermined heating rate; holding the glass article at the second holding temperature for a second duration, wherein from the start of heating the glass article from the first holding temperature to the entire second duration, monitoring the density of the glass article; when the absolute value of the density change rate of the glass article is less than or equal to 0.10 (g / cm 3 ) / min, the second duration ends.
[0012] The second aspect includes the method of the first aspect, wherein when the absolute value of the density change rate of the glass article is equal to 0.00 (g / cm 3 ) / min, the second duration ends.
[0013] A third aspect includes the method of any of the first and second aspects, wherein the viscosity of the glass article is maintained within a logarithmic viscosity ±0.1 poise of the target viscosity for the first predetermined duration.
[0014] A fourth aspect includes the method of any one of aspects 1 to 3, wherein the viscosity of the glass article is maintained within a logarithmic viscosity ±1.0 poise of the target viscosity during at least a portion of the time the glass article is heated from the first holding temperature to the second holding temperature.
[0015] A fifth aspect includes the method of any one of aspects 1 to 4, wherein data from an automated viscosity control system is used to maintain the viscosity of the glass article within a log viscosity ±1.0 poise of the target viscosity for a first predetermined duration.
[0016] A sixth aspect includes the method of any one of aspects 1 to 5, wherein the density of the glass article is monitored in situ during heating the glass article from the first holding temperature to the second holding temperature and holding the glass article at the second holding temperature for a second duration.
[0017] A seventh aspect includes the method of aspect six, wherein the density of the glass article is monitored in situ with a dilatometer during heating the glass article from the first hold temperature to the second hold temperature at a second predetermined heating rate and holding the glass article at the second hold temperature for a second duration.
[0018] An eighth aspect includes the method of any one of aspects 1 to 7, wherein the second duration ends when the density of the glass article is constant for at least 15 minutes, or preferably at least 50 minutes.
[0019] A ninth aspect includes the method of any one of aspects 1 to 8, wherein the second duration ends when the density of the glass article is constant for at least 100 minutes.
[0020] A tenth aspect includes the method of any of aspects one through nine, wherein the first predetermined heating rate is determined based at least in part on performance of an automated viscosity control system.
[0021] An eleventh aspect includes the method of any of the first to tenth aspects, wherein the second predetermined heating rate is determined based at least in part on performance of the automatic viscosity control system.
[0022] A twelfth aspect includes the method of any one of aspects 1 to 11, further comprising applying a weight restraining force to the glass article.
[0023] A thirteenth aspect includes the method of any one of aspects one through twelfth, wherein the glass article is part of a glass stack.
[0024] A fourteenth aspect includes the method of aspect thirteen, wherein the glass stack comprises: a first positioner; a plurality of glass sheets placed on the first positioner; and a second positioner positioned on the stack of glass sheets.
[0025] A fifteenth aspect includes the method of aspect fourteen, wherein the plurality of glass sheets includes at least ten glass sheets.
[0026] A sixteenth aspect includes the method of aspect fourteen, wherein the plurality of glass sheets includes at least 20 glass sheets.
[0027] A seventeenth aspect includes the method of any one of aspects one through eighteen, wherein the temperature difference of the glass article from the programmed temperature is within ±8° C. during the first predetermined duration.
[0028] An eighteenth aspect includes the method of any one of aspects one through seventeen, wherein the temperature difference of the glass article from the programmed temperature is within ±5° C. during the first predetermined duration.
[0029] A nineteenth aspect includes the method of any one of aspects one through eighteen, wherein during the second duration, the temperature difference of the glass article from the programmed temperature is within ±8°C.
[0030] A twentieth aspect includes the method of any one of aspects one to nineteen, wherein during the second duration, the temperature difference between the glass article and the programmed temperature is within ±5°C.
[0031] A twenty-first aspect includes the method of any of aspects one through twentieth, wherein heating the glass article to the first hold temperature at the first predetermined heating rate comprises multi-stage heating.
[0032] A twenty-second aspect includes the method of any one of aspects one to twenty-first, wherein during heating of the glass article to the first holding temperature at the first predetermined heating rate, the viscosity of the glass article is maintained at a log viscosity greater than or equal to 11.0 poise.
[0033] A twenty-third aspect includes the method of any one of aspects one through twenty-second, wherein the viscosity of the glass article is maintained at a logarithmic viscosity of greater than or equal to 11.0 poise for the first predetermined duration.
[0034] A twenty-fourth aspect includes the method of any one of aspects one through twenty-third, wherein during heating of the glass article at the first predetermined heating rate to the first holding temperature, the viscosity of the glass article is maintained at a log viscosity greater than or equal to 11.0 poise.
[0035] A twenty-fifth aspect includes the method of any one of aspects one through twenty-fourth, wherein the viscosity of the glass article is maintained at a log viscosity of greater than or equal to 11.0 poise throughout the duration of the method.
[0036] A twenty-sixth aspect includes the method of any one of aspects 1 to 25, wherein the viscosity of the glass article is maintained at a log viscosity of greater than or equal to 11.0 poise throughout the duration of the method.
[0037] Additional features and advantages are set forth in the following detailed description, some of which will be readily apparent to those skilled in the art from that description or may be recognized by practicing the various embodiments described herein, including the following detailed description, claims, and accompanying drawings.
[0038] It should be understood that both the foregoing general description and the following detailed description describe various embodiments and are intended to provide an overall review or framework for understanding the nature and character of the claimed subject matter. The accompanying drawings are included to provide a further understanding of the various embodiments and are incorporated in and constitute a part of this specification. The accompanying drawings illustrate the various embodiments described herein and, together with the description, are used to explain the principles and operation of the claimed subject matter. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 schematically depicts a glass stack according to embodiments disclosed and described herein;
[0040] Figure 2A graphically depicting temperature versus time measurements and nucleation and crystallization (growth) for a ceramization cycle according to embodiments disclosed and described herein;
[0041] Figure 2B graphically depicting the relationship between nucleation rate and crystal growth rate versus temperature during a ceramization cycle according to embodiments disclosed and described herein;
[0042] Figure 3 is a flow chart of proportional-integral-derivative (PID) logic used in the automatic viscosity control (AVC) nucleation phase of a ceramization cycle according to embodiments disclosed and described herein;
[0043] Figure 4 is a block diagram illustrating a system for manipulating the AVC nucleation phase of a ceramization cycle according to embodiments disclosed and described herein;
[0044] Figure 5 graphically depicting log viscosity (in poise) versus time (in minutes) during a ceramization cycle according to embodiments disclosed and described herein;
[0045] Figure 6 graphically depicting temperature (in degrees Celsius) versus time (in minutes) during a ceramization cycle according to embodiments disclosed and described herein;
[0046] Figure 7 schematically illustrates a dilatometer that can be used in situ to measure the density of a glass article according to embodiments disclosed and described herein;
[0047] Figure 8 graphically depicts density (in grams per cubic centimeter) versus time (in minutes) during a ceramization cycle according to embodiments disclosed and described herein;
[0048] Fig. 9 graphically depicts density (in grams per cubic centimeter) versus time (in minutes) during a ceramization cycle according to embodiments disclosed and described herein;
[0049] Fig.10 graphically depicting viscosity (in log10 poise) versus time (in minutes) during a ceramization cycle according to embodiments disclosed and described herein;
[0050] Fig.11 Graphically depicting the relationship of temperature (on the left y-axis in degrees Celsius) relative to time (on the y-axis in hours), and the relationship of viscosity (on the right y-axis in log10 poise) relative to time (on the x-axis in hours) during a ceramization cycle according to embodiments disclosed and described herein;
[0051] Fig. 12A shows the warpage of a glass ceramic article ceramized by a ceramizing cycle according to embodiments disclosed and described herein;
[0052] Fig. 12B shows the warpage of a glass ceramic article ceramized by a ceramizing cycle according to embodiments disclosed and described herein;
[0053] Fig. 12C shows the warpage of a glass ceramic article ceramized by a ceramizing cycle according to embodiments disclosed and described herein;
[0054] Fig.13A shows the warpage of a glass ceramic article ceramized by a ceramizing cycle according to embodiments disclosed and described herein;
[0055] Fig. 13B shows the warpage of a glass ceramic article ceramized by a ceramizing cycle according to embodiments disclosed and described herein;
[0056] Fig. 13C shows the warpage of a glass ceramic article ceramized by a ceramizing cycle according to embodiments disclosed and described herein;
[0057] Fig.14 graphically depicting the viscosity sag (in mm) of a glass-ceramic article ceramized by a ceramizing cycle according to embodiments disclosed and described herein versus the radius of a disk (in mm);
[0058] Fig.15A graphically depicts the horizontal position of a measuring device within a chamber of a heating device according to embodiments disclosed and described herein;
[0059] Fig. 15B graphically depicts the vertical position of a measurement device within a chamber of a heating apparatus according to embodiments disclosed and described herein;
[0060] Fig.16 graphically depicts temperature (in degrees Celsius) recorded by a measuring device in a cavity chamber of a heating apparatus versus time (in seconds) according to embodiments disclosed and described herein;
[0061] Fig.17 Graphically depicting the temperature of a glass sheet (on the left y-axis in degrees Celsius) versus time (on the x-axis in seconds) and the temperature difference between glass sheets (on the right y-axis in degrees Celsius) versus time (on the x-axis in seconds) when ceramicizing according to a ceramicizing cycle of embodiments disclosed and described herein;
[0062] Fig.18 graphically depicting temperature (in degrees Celsius) versus time (in seconds) for a glass piece ceramized through a ceramizing cycle according to embodiments disclosed and described herein, including expanded views of various portions of the diagram of the glass article;
[0063] Fig.19 graphically depicting the effect of multi-stage heating on the temperature difference of a glass sheet (in degrees Celsius) versus time (in minutes) according to embodiments disclosed and described herein;
[0064] Fig. 20 graphically depicting the effect of multi-stage heating on the temperature difference of a glass sheet (in degrees Celsius) versus time (in minutes) according to embodiments disclosed and described herein;
[0065] Fig.21 graphically depicting the effect of multi-stage heating on the temperature difference of a glass sheet (in degrees Celsius) versus time (in minutes) according to embodiments disclosed and described herein;
[0066] Fig. 22 graphically depicting temperature (in degrees Celsius) versus time (in minutes) for a ceramizing cycle according to embodiments disclosed and described herein and a conventional ceramizing cycle;
[0067] Fig.23 The density (in grams per cubic centimeter) versus time (in minutes) for a ceramizing cycle according to embodiments disclosed and described herein and a conventional ceramizing cycle is graphically depicted. Detailed Description
[0068] The method for ceramicizing a glass product will be described in detail below, and its embodiments are shown in the accompanying drawings. Wherever possible, the same reference numerals are used to indicate the same or similar parts in all drawings. In one embodiment, a method for ceramicizing a glass product into a glass ceramic includes: placing the glass product in a heating device; heating the glass product to a first holding temperature at a first predetermined heating rate; maintaining the glass product at a first predetermined duration at a first holding temperature, wherein during the first predetermined duration, the viscosity of the glass product is maintained within the range of ±1.0 poise of the logarithmic viscosity of the target viscosity; heating the glass product from the first holding temperature to a second holding temperature at a second predetermined heating rate; maintaining the glass product at a second holding temperature for a second duration, wherein the density of the glass product is monitored from the heating of the glass product at the first holding temperature to the entire second duration; when the density of the glass product is constant, the second duration ends. Various embodiments for ceramicizing a glass product will be described herein with specific reference to the accompanying drawings.
[0069] Generally, methods for forming glass-ceramics include forming a glass article and ceramizing the glass article to convert the glass article into a glass-ceramic form. Figure 1 , an exemplary stacking structure 100 for ceramicization is shown. The stacking structure 100 includes a carrier plate 102 supporting two positioning plates 104 and a glass stack 106 located between the positioning plates 104.
[0070] In some embodiments, an insulating layer (not shown) may be located on the top surface of the upper positioning plate 104 and on the bottom surface of the lower positioning plate 104. The insulating layer may be formed of any material having a low thermal conductivity and may reduce or even eliminate the axial temperature gradient of the glass sheets 108 on the top and bottom of the glass stack 106.
[0071] like Figure 1 As shown, the glass stack 106 includes a plurality of glass sheets 108, each glass sheet 108 being separated from adjacent glass sheets 108 by a release agent layer 110. The release agent layer 110 reduces or even eliminates the adhesion of the glass sheets 108 in the glass stack 106 during the ceramization process. Figure 1 , in some embodiments, the glass stack 106 may further include a release agent layer 110 between the glass sheet 108 and the positioning plate 104. In other embodiments, such as the various embodiments described below, the positioning plate 104 is made of a material that does not react with the glass sheet 108, and the release agent layer 110 is not required to prevent interaction between the glass sheet 108 and the positioning plate 104.
[0072] Typically, in order to form glass ceramics, the glass stack 106 is heated at a temperature above its annealing point for a time sufficient to form a crystal nucleus (also referred to as "nucleation"). Heat treatment can be carried out in, for example, an annealing furnace or a heating furnace. After being heated to a temperature above its annealing point, the glass is typically further heated at a higher temperature between the glass annealing point and the glass softening point to form a crystalline phase (also referred to as "growth" or "crystallization"). In various embodiments, the heat treatment or ceramicization process includes heating the glass stack to a nucleation temperature, maintaining the nucleation temperature for a predetermined time period, heating the glass stack to a crystallization temperature, and maintaining the crystallization temperature for a predetermined time period.
[0073] The glass sheet 108 can be made of any glass composition suitable for forming a glass-ceramic article, but it should be understood that the glass composition of the glass sheet 108 may affect the mechanical and optical properties of the glass-ceramic article. In various embodiments, the glass composition is selected so that the resulting glass-ceramic article has a petalite crystalline phase and a lithium silicate crystalline phase, wherein the petalite crystalline phase and the lithium silicate crystalline phase have a higher weight percentage than other crystalline phases present in the glass-ceramic article.
[0074] By way of example and not limitation, in various embodiments, the glass sheet 108 can be formed of a glass composition comprising approximately 55 wt % to approximately 80 wt % SiO2, approximately 2 wt % to approximately 20 wt % Al2O3, approximately 5 wt % to approximately 20 wt % Li2O, approximately 0 wt % to approximately 10 wt % B2O3, approximately 0 wt % to approximately 5 wt % Na2O, approximately 0 wt % to approximately 10 wt % ZnO, approximately 0.5 wt % to approximately 6 wt % P2O5, and approximately 0.2 wt % to approximately 15 wt % ZrO2.
[0075] The oxide SiO2 involved in forming glass can play a role in stabilizing the network structure of glass and glass ceramics. In various glass compositions, the concentration of SiO2 should be high enough to form a petalite crystalline phase when the glass sheet is heat-treated to be converted into glass ceramics. Since the melting temperature of pure SiO2 or high SiO2 glass is too high, the amount of SiO2 can be limited to control the melting temperature of the glass. In some embodiments, the glass or glass ceramic composition comprises about 55% by weight to about 80% by weight of SiO2. In some embodiments, the glass or glass ceramic composition comprises about 69% by weight to about 80% by weight of SiO2. In some embodiments, the glass or glass-ceramic composition can include about 55 wt % to about 80 wt %, about 55 wt % to about 77 wt %, about 55 wt % to about 75 wt %, about 55 wt % to about 73 wt %, about 60 wt % to about 80 wt %, about 60 wt % to about 77 wt %, about 60 wt % to about 75 wt %, about 60 wt % to about 73 wt %, about 69 wt % to about 80 wt %, about 69 wt % to about 77 wt %, about 69 wt % to about 75 wt %, about 60 wt % to about 73 wt %, % to about 80 wt %, about 70 wt % to about 77 wt %, about 70 wt % to about 75 wt %, about 70 wt % to about 73 wt %, about 73 wt % to about 80 wt %, about 73 wt % to about 77 wt %, about 73 wt % to about 75 wt %, about 75 wt % to about 80 wt %, about 75 wt % to about 77 wt %, or about 77 wt % to about 80 wt % SiO2, and any and all subranges formed by any of the foregoing endpoints.
[0076] Al2O3 can also stabilize the network and also improve mechanical properties and chemical resistance. However, if the content of Al2O3 is too high, the proportion of lithium silicate crystals may be reduced, possibly to the extent that an interlocking structure cannot be formed. The content of Al2O3 can be adjusted to control the viscosity. In addition, if the content of Al2O3 is too high, the viscosity of the melt is also generally increased. In some embodiments, the glass or glass ceramic composition comprises about 2 wt % to about 20 wt % Al2O3. In some embodiments, the glass or glass ceramic composition comprises about 6 wt % to about 9 wt % Al2O3. In some embodiments, the glass or glass ceramic composition can include about 2 wt % to about 20 wt %, about 2 wt % to about 18 wt %, about 2 wt % to about 15 wt %, about 2 wt % to about 12 wt %, about 2 wt % to about 10 wt %, about 2 wt % to about 9 wt %, about 2 wt % to about 8 wt %, about 2 wt % to about 5 wt %, about 5 wt % to about 20 wt %, about 5 wt % to about 18 wt %, about 5 wt % to about 15 wt %, about 5 wt % to about 12 wt %, about 5 wt % to about 10 wt %, about 5 wt % to about 9 wt %, about 5 wt % to about 8 wt %, about 6 wt % to about 20 wt %, about 6 wt % to about 18 wt %, about 6 wt % to about 15 wt %, about 6 wt % to about 12 wt %, about 6 wt % to about 10 wt %, about 6 wt % to about 9 wt %, about 6 wt % to about 8 wt %, about % to about 15 wt %, about 6 wt % to about 12 wt %, about 6 wt % to about 10 wt %, about 6 wt % to about 9 wt %, 8 wt % to about 20 wt %, about 8 wt % to about 18 wt %, about 8 wt % to about 15 wt %, about 8 wt % to about 12 wt %, about 8 wt % to about 10 wt %, 10 wt % to about 20 wt %, about 10 wt % to about 18 wt %, about 10 wt % to about 15 wt %, about 10 wt % to about 12 wt %, about 12 wt % to about 20 wt %, about 12 wt % to about 18 wt %, or about 12 wt % to about 15 wt % Al2O3, and any and all subranges formed by any of the foregoing endpoints.
[0077] In the glasses and glass ceramics described herein, Li2O contributes to the formation of petalite and lithium silicate crystalline phases. In fact, in order to obtain petalite and lithium silicate as the main crystalline phases, it is desirable to have at least about 7 wt% Li2O in the composition. It has also been found that once the Li2O content becomes too high (greater than about 15 wt%), the composition becomes very fluid. Therefore, in some embodiments, the glass or glass ceramic composition comprises about 5 wt% to about 20 wt% Li2O. In other embodiments, the glass or glass ceramic composition comprises about 10 wt% to about 14 wt% Li2O. In some embodiments, the glass or glass-ceramic composition can include from about 5 wt % to about 20 wt %, from about 5 wt % to about 18 wt %, from about 5 wt % to about 16 wt %, from about 5 wt % to about 14 wt %, from about 5 wt % to about 12 wt %, from about 5 wt % to about 10 wt %, from about 5 wt % to about 8 wt %, from about 7 wt % to about 20 wt %, from about 7 wt % to about 18 wt %, from about 7 wt % to about 16 wt %, from about 7 wt % to about 14 wt %, from about 7 wt % to about 12 wt %, from about 7 wt % to about 10 wt %, from about 10 wt % to about 20 wt %, from about 10 wt % to about 1 % to about 8 wt%, about 10 wt% to about 16 wt%, about 10 wt% to about 14 wt%, about 10 wt% to about 12 wt%, about 12 wt% to about 20 wt%, about 12 wt% to about 18 wt%, about 12 wt% to about 16 wt%, about 12 wt% to about 14 wt%, about 14 wt% to about 20 wt%, about 14 wt% to about 18 wt%, about 14 wt% to about 16 wt%, about 16 wt% to about 20 wt%, about 16 wt% to about 18 wt%, or about 18 wt% to about 20 wt% Li2O, and any and all subranges formed by any of the foregoing endpoints.
[0078] As described above, Li2O is generally useful for forming various glass ceramics, but other alkali metal oxides tend to reduce the formation of glass ceramics and form aluminosilicate residual glass in glass ceramics. It has been found that greater than about 5 wt% of Na2O or K2O or a combination thereof results in an unfavorable amount of residual glass, which may result in deformation and undesirable microstructures during crystallization from a mechanical properties perspective. The composition of the residual glass can be adjusted to control the viscosity during crystallization, minimize deformation or undesirable thermal expansion, or control microstructural properties. Therefore, the glass sheet can generally be made of a glass composition having a small amount of non-lithium alkali metal oxide. In some embodiments, the glass or glass ceramic composition may include about 0 wt% to about 5 wt% of R2O, wherein R is one or more of alkali metal cations Na and K. In some embodiments, the glass or glass ceramic composition may include about 1 wt% to about 3 wt% of R2O, wherein R is one or more of alkali metal cations Na and K. In some embodiments, the glass or glass ceramic composition can include 0 wt % to about 5 wt %, 0 wt % to about 4 wt %, 0 wt % to about 3 wt %, 0 wt % to about 2 wt %, 0 wt % to about 1 wt %, > 0 wt % to about 5 wt %, > 0 wt % to about 4 wt %, > 0 wt % to about 3 wt %, > 0 wt % to about 2 wt %, > 0 wt % to about 1 wt %, about 1 wt % to about 5 wt %, about 1 wt % to about 4 wt %, about 1 wt % to about 3 wt %, about 1 wt % to about 2 wt %, about 2 wt % to about 5 wt %, about 2 wt % to about 4 wt %, about 2 wt % to about 3 wt %, about 3 wt % to about 5 wt %, about 3 wt % to about 4 wt %, or about 4 wt % to about 5 wt % Na2O, KO, or combinations thereof, and any and all subranges formed by any of the preceding endpoints.
[0079] Glass and glass-ceramic compositions may include P2O5. P2O5 may act as a nucleating agent, promoting bulk nucleation. If the concentration of P2O5 is too low, although the precursor glass does crystallize, it only crystallizes at higher temperatures (due to lower viscosity) and from the surface inward, resulting in a weak and often deformed object. However, if the concentration of P2O5 is too high, devitrification may be difficult to control when cooling during the formation of the glass sheet. Embodiments may include >0 wt% to about 6 wt% P2O5. Other embodiments may include >2 wt% to about 4 wt% P2O5. Still other embodiments may include >1.5 wt% to about 2.5 wt% P2O5. In some embodiments, the glass or glass ceramic composition can include 0 wt % to about 6 wt %, 0 wt % to about 5.5 wt %, 0 wt % to 5 wt %, 0 wt % to about 4.5 wt %, 0 wt % to about 4 wt %, 0 wt % to about 3.5 wt %, 0 wt % to about 3 wt %, 0 wt % to about 2.5 wt %, 0 wt % to about 2 wt %, 0 wt % to about 1.5 wt %, 0 wt % to about 1 wt %, > 0 wt % to about 6 wt %, > 0 wt % to about 5.5 wt %, > 0 wt % to 5 wt %, > 0 wt % to about 4.5 wt %, >0 wt % to about 4 wt %, >0 wt % to about 3.5 wt %, >0 wt % to about 3 wt %, >0 wt % to about >2.5 wt %, 0 wt % to about 2 wt %, >0 wt % to about 1.5 wt %, >0 wt % to about 1 wt %, about 0.5 wt % to about 6 wt %, about 0.5 wt % to about 5.5 wt %, about 0.5 wt % to 5 wt %, about 0.5 wt % to about 4.5 wt %, about 0.5 wt % to about 4 wt %, about 0.5 wt % to about 3.5 wt %, about 0.5% to about 3% by weight, about 0.5% to about 2.5% by weight, about 0.5% to about 2% by weight, about 0.5% to about 1.5% by weight, about 0.5% to about 1% by weight, about 1% to about 6% by weight, about 1% to about 5.5% by weight, about 1% to about 5% by weight, about 1% to about 4.5% by weight, about 1% to about 4% by weight, about 1% to about 3.5% by weight, about 1% to about 3% by weight, about 1% to about 2.5% by weight, about 1% to about 2% by weight, about 1 wt % to about 1.5 wt %, about 1.5 wt % to about 6 wt %, about 1.5 wt % to about 5.5 wt %, about 1.5 wt % to about 5 wt %, about 1.5 wt % to about 4.5 wt %, about 1.5 wt % to about 4 wt %, about 1.5 wt % to about 3.5 wt %, about 1.5 wt % to about 3 wt %, about 1.5 wt % to about 2.5 wt %, about 1.5 wt % to about 2 wt %, about 2 wt % to about 6 wt %, about 2 wt % to about 5.5 wt %, about 2 wt % to about 4.5 wt %, about 1.5 wt % to about 4.5 wt %,5 wt %, about 2 wt % to about 4 wt %, about 2 wt % to about 3.5 wt %, about 2 wt % to about 3 wt %, about 2 wt % to about 2.5 wt %, about 2.5 wt % to about 6 wt %, about 2.5 wt % to about 5.5 wt %, about 2.5 wt % to 5 wt %, about 2.5 wt % to about 4.5 wt %, about 2.5 wt % to about 4 wt %, about 2.5 wt % to about 3.5 wt %, about 2.5 wt % to about 3 wt %, about 3 wt % to about 6 wt %, about 3 wt % to about 5.5 wt %, about 3 wt % to 5 wt %, about 3 wt % to about 4.5 wt %, about 3 wt % to about 4.5 wt %, about 3 wt % to about 3.5 wt % , about 3.5 wt% to about 6 wt%, about 3.5 wt% to about 5.5 wt%, about 3.5 wt% to about 5 wt%, about 3.5 wt% to about 4.5 wt%, about 3.5 wt% to about 4 wt%, about 4 wt% to about 6 wt%, about 4 wt% to about 5.5 wt%, about 4 wt% to 5 wt%, about 4 wt% to about 4.5 wt%, about 4.5 wt% to about 6 wt%, about 4.5 wt% to about 5.5 wt%, about 4.5 wt% to about 5.5 wt%, about 4.5 wt% to about 5 wt%, about 5 wt% to about 6 wt%, about 5 wt% to about 5.5 wt%, or about 5.5 wt% to about 6 wt% P2O5, and any and all subranges formed by any of the preceding endpoints. .
[0080] In various glass and glass ceramic compositions, ZrO2 is generally found to improve the stability of Li2O—Al2O3—SiO2—P2O5 glass by significantly reducing glass devitrification during forming and lowering the liquidus temperature. At concentrations above 8 wt%, ZrSiO4 can form a primary liquidus phase at high temperatures, which significantly reduces the liquidus viscosity. When the glass contains more than 2 wt% ZrO2, a transparent glass can be formed. The addition of ZrO2 can also help reduce the petalite grain size, which helps to form transparent glass ceramics. In some embodiments, the glass or glass ceramic composition contains about 0.2 wt% to about 15 wt% ZrO2. In some embodiments, the glass or glass ceramic composition contains about 2 wt% to about 4 wt% ZrO2. In some embodiments, the glass or glass-ceramic composition can include from about 0.2 wt % to about 15 wt %, from about 0.2 wt % to about 12 wt %, from about 0.2 wt % to about 10 wt %, from about 0.2 wt % to about 8 wt %, from about 0.2 wt % to about 6 wt %, from about 0.2 wt % to about 4 wt %, from about 0.5 wt % to about 15 wt %, from about 0.5 wt % to about 12 wt %, from about 0.5 wt % to about 10 wt %, from about 0.5 wt % to about 8 wt %, from about 0.5 wt % to about 6 wt %, from about 0.5 wt % to about 4 wt %, from about 1 wt % to about 15 wt %, from about 1 wt % to about 12 wt %, from about 1 wt % to about 10 wt %, from about 1 wt % to about 8 wt %, from about 1 wt % to about 6 wt %, from about 1 wt % to about 4 wt %, from about 2 wt % to about 15 wt %, from about 2 wt % to about 12 wt %. % to about 8 wt %, about 2 wt % to about 6 wt %, about 2 wt % to about 4 wt %, about 3 wt % to about 15 wt %, about 3 wt % to about 12 wt %, about 3 wt % to about 10 wt %, about 3 wt % to about 8 wt %, about 3 wt % to about 6 wt %, about 3 wt % to about 4 wt %, about 4 wt % to about 15 wt %, about 4 wt % to about 12 wt %, about 4 wt % to about 10 wt %, about 4 wt % to about 8 wt %, about 4 wt % to about 6 wt %, about 8 wt % to about 15 wt %, about 8 wt % to about 12 wt %, about 8 wt % to about 10 wt %, about 10 wt % to about 15 wt %, about 10 wt % to about 12 wt %, or about 12 wt % to about 15 wt % ZrO2, and any and all subranges formed by any of the foregoing endpoints.
[0081] B2O3 is conducive to providing a glass sheet with a low melting temperature. In addition, adding B2O3 in the glass sheet and thus in the glass ceramic product helps to achieve an interlocking crystal microstructure, and can also improve the damage resistance of the glass ceramic product. When the boron in the residual glass is not balanced by alkali metal oxides or divalent cation oxides, it will be in a triangular coordination state (or tri-coordinate boron), which opens the structure of the glass. The network around these three coordinated borons does not have the rigidity of tetrahedral coordination (or tetra-coordinate) boron. Without being bound by theory, it is believed that glass sheets and glass ceramics containing tri-coordinate boron can allow a certain degree of deformation before cracks are formed. By allowing some deformation, the Vickers indentation crack initiation value (Vickersindentation crack initiation value) is improved. The fracture toughness of glass sheets and glass ceramics containing tri-coordinate boron can also be improved. Without being bound by theory, it is believed that the presence of boron in the residual glass of glass ceramics (and glass sheets) can reduce the viscosity of the residual glass (or glass sheets), thereby promoting the growth of lithium silicate crystals, particularly large crystals with a high aspect ratio. It is believed that a large amount of three-coordinated boron (relative to four-coordinated boron) causes glass-ceramics to have a larger Vickers indentation crack initiation load. In some embodiments, the content of three-coordinated boron (accounting for total B2O3 percentage) can be about 40% or greater, 50% or greater, 75% or greater, 85% or greater, even 95% or greater. The content of boron should usually be controlled to keep the chemical tolerance and the mechanical strength of the ceramicized bulk glass-ceramics.
[0082] In one or more embodiments, the glass or glass-ceramic composition comprises 0 wt % to about 10 wt % or 0 wt % to about 2 wt % B2O3. In some embodiments, the glass or glass-ceramic composition may comprise 0 wt % to about 10 wt %, 0 wt % to about 9 wt %, 0 wt % to about 8 wt %, 0 wt % to about 7 wt %, 0 wt % to about 6 wt %, 0 wt % to about 5 wt %, 0 wt % to about 4 wt %, 0 wt % to about 3 wt %, 0 wt % to about 2 wt %, 0 wt % to about 1 wt %, >0 wt % to about 10 wt %, >0 wt % to about 9 wt %, >0 wt % to about 8 wt %, >0 wt % to about 7 wt %, >0 wt % to about 6 wt %, >0 wt % to about 5 wt %, >0 wt % to about 4 wt %, >0 wt % to about 3 wt %, >0 wt % to about 2 wt %, >0 wt % to about 1 wt %, or about 1 wt %. % to about 10 wt %, about 1 wt % to about 8 wt %, about 1 wt % to about 6 wt %, about 1 wt % to about 5 wt %, about 1 wt % to about 4 wt %, about 1 wt % to about 2 wt %, about 2 wt % to about 10 wt %, about 2 wt % to about 8 wt %, about 2 wt % to about 6 wt %, about 2 wt % to about 4 wt %, about 3 wt % to about 10 wt %, about 3 wt % to about 8 wt %, about 3 wt % to about 6 wt %, about 3 wt % to about 4 wt %, about 4 wt % to about 5 wt %, about 5 wt % to about 8 wt %, about 5 wt % to about 7.5 wt %, about 5 wt % to about 6 wt %, or about 5 wt % to about 5.5 wt % B2O3, and any and all subranges formed by any of the preceding endpoints.
[0083] MgO can enter the petalite crystal in the form of a partial solid solution. In some embodiments, the glass or glass-ceramic composition includes about 0 wt % to about 8 wt % MgO. In some embodiments, the glass or glass-ceramic composition may include 0 wt % to about 8 wt %, 0 wt % to about 7 wt %, 0 wt % to about 6 wt %, 0 wt % to about 5 wt %, 0 wt % to about 4 wt %, 0 wt % to about 3 wt %, 0 wt % to about 2 wt %, 0 wt % to about 1 wt %, about 1 wt % to about 8 wt %, about 1 wt % to about 7 wt %, about 1 wt % to about 6 wt %, about 1 wt % to about 5 wt %, about 1 wt % to about 4 wt %, about 1 wt % to about 3 wt %, about 1 wt % to about 2 wt %, about 2 wt % to about 8 wt %, about 2 wt % to about 7 wt %, about 2 wt % to about 6 wt %, about 2 wt % to about 6 wt %, about 2 wt % to about % to about 5 wt %, about 2 wt % to about 4 wt %, about 2 wt % to about 3 wt %, about 3 wt % to about 8 wt %, about 3 wt % to about 7 wt %, about 3 wt % to about 6 wt %, about 3 wt % to about 5 wt %, about 3 wt % to about 4 wt %, about 4 wt % to about 8 wt %, about 4 wt % to about 7 wt %, about 4 wt % to about 6 wt %, about 4 wt % to about 5 wt %, about 5 wt % to about 8 wt %, about 5 wt % to about 7 wt %, about 5 wt % to about 6 wt %, about 6 wt % to about 8 wt %, about 6 wt % to about 7 wt %, or about 7 wt % to about 8 wt % MgO, and any and all subranges formed by any of the preceding endpoints.
[0084] ZnO can be incorporated into the petalite crystals as a partial solid solution. In one or more embodiments, the glass or glass ceramic composition comprises from about 0 wt % to about 10 wt % ZnO. In some embodiments, the glass or glass-ceramic composition can include 0 wt % to about 10 wt %, 0 wt % to about 9 wt %, 0 wt % to about 8 wt %, 0 wt % to about 7 wt %, 0 wt % to about 6 wt %, 0 wt % to about 5 wt %, 0 wt % to about 4 wt %, 0 wt % to about 3 wt %, 0 wt % to about 2 wt %, 0 wt % to about 1 wt %, about 1 wt % to about 10 wt %, about 1 wt % to about 9 wt %, about 1 wt % to about 8 wt %, about 1 wt % to about 7 wt %, about 1 wt % to about 6 wt %, about 1 wt % to about 5 wt %, about 1 wt % to about 4 wt %, about 1 wt % to about 3 wt %, about 1 wt % to about 2 wt %, about 2 wt % to about 10 wt %, about 2 wt % to about 9 wt %, about 2 wt % to about 8 wt %, about 2 wt % to about 7 wt %, about 2 wt % to about 6 wt %, about 2 wt % to about 5 wt %, about 2 wt % to about 4 wt %, about 2 wt % to about 3 wt %, about 3 wt % to about 10 wt %. % to about 7 wt %, about 3 wt % to about 6 wt %, about 3 wt % to about 5 wt %, about 3 wt % to about 4 wt %, about 4 wt % to about 10 wt %, about 4 wt % to about 9 wt %, about 4 wt % to about 8 wt %, about 4 wt % to about 7 wt %, about 4 wt % to about 6 wt %, about 4 wt % to about 5 wt %, about 5 wt % to about 10 wt %, about 5 wt % to about 9 wt %, about 5 wt % to about 8 wt %, about 5 wt % to about 7 wt %, about 5 wt % to about 6 wt %, about 6 wt % to about 10 wt %, about 6 wt % to about 9 wt %, about 6 wt % to about 8 wt %, about 6 wt % to about 7 wt %, about 7 wt % to about 10 wt %, about 7 wt % to about 9 wt %, about 7 wt % to about 8 wt %, about 8 wt % to about 10 wt %, about 8 wt % to about 9 wt , or about 9 wt % to about 10 wt % ZnO, and any and all subranges formed by any of the foregoing endpoints.
[0085] In various embodiments, the glass or glass ceramic composition may further include one or more components, such as but not limited to TiO2, CeO2 and SnO2. Additionally or alternatively, an antimicrobial component may be added to the glass or glass ceramic composition. The antimicrobial component that can be added to the glass or glass ceramic may include but is not limited to Ag, AgO, Cu, CuO, Cu2O, etc. In some embodiments, the glass or glass ceramic composition may further include a chemical clarifier. Such clarifiers include but are not limited to SnO2, As2O3, Sb2O3, F, Cl and Br. Other details of the glass and / or glass-ceramic composition applicable to various embodiments can be found in, for example, U.S. Patent Application Publication No. 2016 / 0102010 filed on October 8, 2015, entitled "High Strength Glass-Ceramics Having Petalite and Lithium Silicate Structures", the entire contents of which are incorporated herein by reference.
[0086] In various embodiments, the glass composition can be formed into sheets by methods including, but not limited to, slot drawing, float forming, roller pressing, and other sheet forming methods known to those skilled in the art.
[0087] In order to produce the desired glass-ceramic products, controlled bulk nucleation and growth are essential. Figure 2A As shown, bulk nucleation (including homogeneous and heterogeneous) is performed at an elevated temperature for a certain period of time. Historically, the nucleation temperature and time are empirically selected to be above the glass transition temperature (Tg) or annealing temperature, such as Figure 2B As shown. Similarly, the growth temperature and time above the nucleation temperature are also selected empirically. The optimized time and temperature can be achieved by changing the time and temperature of the nucleation and growth stages during the processing. Nucleation and crystal growth events often overlap. Therefore, physical properties such as viscosity change over time during the nucleation and growth steps. However, when transitioning from the nucleation stage to the growth stage, the rate of increase of density and / or viscosity varies. When the rate of increase of density and / or viscosity changes significantly, the ceramization process may not produce the desired final glass-ceramic product.
[0088] To avoid sagging, sticking or viscous deformation, the time and temperature of the processing cycle should be controlled. Most conventional methods involve trial-and-error based testing in intuitively designed thermal cycles, which are improved by material characterization methods. Some examples of these characterization methods are the use of differential scanning calorimetry or in-situ analysis of X-ray diffraction peaks over time to measure the change in heat flow of the crystallization peak as a function of annealing time. Most of these methods do not help developers find the optimal conditions for dimensional stability, and they are very laborious and time-consuming. To overcome all these shortcomings, an embodiment disclosed and described herein for ceramicizing a glass article automatically determines the ceramicizing cycle that will result in the desired glass-ceramic article. An embodiment of the ceramicizing method includes two analytical tools: (1) an automatic viscosity controller (AVC) for determining the cycle of the nucleation step and the transition heating step from nucleation to crystal growth; (2) a non-contact in-situ density measurement method that determines the duration of crystal growth. Using these two methods, the entire ceramicizing cycle can be directly obtained.
[0089] The goal of automatic viscosity control (AVC) is to keep the glass at a constant viscosity to determine the time-temperature cycle with minimum sag during the ceramicization cycle of the glass. In this embodiment, constant viscosity is maintained by a) calculating the instantaneous viscosity using the deflection rate of the glass beam under constant stress in a three-point beam bending device, and b) dynamically changing the heating / cooling rate using a proportional integral differential (PID) control loop that is used to determine the power output provided to the heating furnace. When the viscosity of the glass product increases, the PID logic automatically increases the temperature, and when the viscosity of the glass product decreases, the PID logic reduces the temperature. The PID control loop ensures that the power output varies with the deviation from the target viscosity, thereby avoiding overshoot. Figure 3 An implementation scheme for implementing AVC software logic is shown. Figure 3 is a PID flow chart showing that the instantaneous temperature rise rate is first calculated using a PID control loop for target viscosity - current measured viscosity. The PID logic then calculates the temperature rise rate in order to calculate the controller set point. Next, it is determined whether the previously calculated set point has changed relative to the last set point. If the calculated set point has changed, the controller set point is changed and the PID logic ends and resets. If the calculated set point has not changed, the PID logic ends and resets.
[0090] Figure 4 The communication between the software logic, the heating furnace and the measuring device according to some embodiments is shown. Based on the idea of constant stress, known geometry and varying furnace temperature, this method is applied to a three-point bending viscometer. Figure 4As shown, a computer (e.g., a PC) is connected to a furnace controller and an analog input device. The furnace controller modifies parameters within the furnace, such as temperature, based on input information received from the PC. The furnace is also connected to a linear variable differential controller (LVDT), which collects output information from the furnace (e.g., output information related to temperature, viscosity, etc.) and transmits this data to the analog input device. As previously described, the PC receives data from the analog input device and calculates a set value, such as a temperature set value, to send to the furnace controller. Using this control, the viscosity of the glass product can be kept relatively constant (e.g., within ±1.0 poise of log viscosity) during the nucleation stage.
[0091] The time-temperature cycle is obtained by defining a target constant viscosity that the glass article is to maintain. In this step (according to some embodiments), the maximum temperature, maximum heating rate, target viscosity, sample geometry, sample size, sample density, total applied load, span size of the three-point bending device are all input information in the software. Then follow the software logic, as referenced Figure 3 As explained, AVC automatically defines a time-temperature schedule until the beam deflection (glass viscosity) exceeds the measurement range. The viscosity measurement range is usually good enough to capture the nucleation step and the transition from the nucleation step to the crystal growth step (heating range change). However, the viscosity measurement cannot accurately capture the crystal growth stage itself.
[0092] Figure 5 An embodiment of a method for determining the viscosity of the sample by AVC for three different viscosities is shown. Figure 5 After the AVC is set to about 11.00 (about 11.00 in the middle), the viscosity is maintained by AVC until the crystal growth rate accelerates (e.g., about 305 minutes). During the crystal growth stage, the AVC heating rate cannot maintain constant viscosity and the viscosity begins to increase. When the deflection drops below the measurable range, viscosity fluctuations are observed due to the limited reliability of the viscosity data. Therefore, the time-temperature cycle determined by AVC should be limited to the time when viscosity cannot be maintained.
[0093] Figure 6 An example of the time-temperature cycle determined by AVC for 5 different target log viscosities 10.7, 10.8, 10.9, 11.0 and 11.1 is shown. Figure 6In the example shown in Figure 1, all cycles reach the same maximum temperature because 800°C is entered as the maximum temperature in the software. Above this temperature, AVC is not expected to control viscosity, so in some embodiments no monitoring or control is performed. Similarly, after the transition is complete, the heating rate is linear and the heating rate value is the same for each composition. This corresponds to the maximum heating rate value provided to the software to avoid overheating when the deflection rate (viscosity) exceeds the measurement range. Therefore, the data obtained from AVC is limited to the initial nucleation range and the nonlinear transition range. Similarly, the data cannot accurately describe the process of the crystal growth stage. In order to measure the process of the crystal growth stage, the in-situ density is monitored.
[0094] According to one or more embodiments, measure the variation of one-dimensional strain with time and temperature, and assume that the glass ceramicization process is isotropic, thus calculate the original density. Therefore, it is believed that there is a linear relationship between volume and one-dimensional strain. Non-contact dilatometer measurement is carried out using the DIL806 optical dilatometer purchased from TA Instruments. Figure 7 A measuring device is schematically shown, which includes a light source that emits light into a tray furnace and emits it to a glass sample. After the emitted light contacts the glass sample, it is transmitted to a detector, which can determine the changes in the light received therein, which can then be used to measure the density of the sample. Basically, this method involves measuring the shadows at both ends of the sample when it is heat treated in a heating furnace. The light source is located on the side of the heating furnace opposite to the detector, and the movement of the shadow is related to the density change during the crystal growth process. Unlike conventional expansion methods, the sample can stand freely on the sample holder without applying external force. According to some embodiments, the ceramicization process typically occurs in the logarithmic viscosity range of 9-12 poise viscosity, where the viscous flow caused by gravity can be ignored on the process time scale.
[0095] According to some embodiments, the nucleation and transition time-temperature cycles determined by the AVC are provided to the optical dilatometer software. The final crystal growth temperature is then changed and an isothermal step input is provided that is longer than any expected crystal growth duration to ensure that the crystal growth process is completed. When the density increase reaches the saturation point, it can be considered that there is no significant change in crystal size, and therefore, viscosity and density are constant over time. This step helps to identify any unwanted crystal formation or unexpected decrease in viscosity above the desired growth temperature. The final ensemble (assemblage) and phase of the glass-ceramic can be determined and compared with the data collected from the density measurement to determine how the process affects the ensemble and phase of the glass-ceramic.
[0096] As used herein, when the absolute value of the density change rate of the glass article is less than or equal to 0.10 (g / cm 3 ) / min, for example, less than or equal to 0.09(g / cm3 ) / min, less than or equal to 0.08(g / cm 3 ) / min, less than or equal to 0.07(g / cm 3 ) / min, less than or equal to 0.06(g / cm 3 ) / min, less than or equal to 0.05(g / cm 3 ) / min, less than or equal to 0.04(g / cm 3 ) / min, less than or equal to 0.03(g / cm 3 ) / min, less than or equal to 0.02(g / cm 3 ) / min, less than or equal to 0.01(g / cm 3 ) / min, or 0.00(g / cm 3 ) / min, the density is considered constant. These ranges include all ranges and subranges included in the broad ranges disclosed above.
[0097] Figure 8 The evolution of density at six different growth temperatures according to one embodiment is shown. When the density reaches a plateau, the process is considered to be complete or nearly complete, which can be confirmed with the help of other characterization methods (such as X-ray diffraction (XRD)) and used as the duration of the last step of the ceramization process. At high temperatures (i.e., 780°C and 800°C), non-monotonic changes in density occur, which may be due to the formation of undesirable phases or phase separation.
[0098] According to some embodiments, it is desirable to adjust the ceramizing cycle of the glass-ceramic to achieve minimal warping. Fig. 9 In situ density measurements of glass ceramics during the ceramizing process are shown for various ceramizing schedules. Fig. 9 , a plot of density in grams per cubic centimeter (on the y-axis) versus time in minutes (on the x-axis) is shown. The plot shows that during the nucleation, heating, and growth stages, the glass article undergoes not only temperature-dependent thermal expansion and contraction, but also dynamic, time-dependent, non-thermal contraction. Fig. 9 As shown, during the nucleation hold at constant temperature (i.e., from about 100 minutes to about 350 minutes), the part shrinks due to material changes, which is indicated by an increase in density. During the temperature increase from nucleation to growth, the density is observed to first decrease and then increase rapidly, the latter being due to the material shrinkage caused by rapid crystallization.
[0099] Fig.10 Shown in accordance with Fig. 9 In-situ viscosity measurements of glass ceramics during ceramization for various ceramization cycles of the illustrated embodiment. Fig.10In the graph, the y-axis represents logarithmic viscosity (log 10) poise and the x-axis represents the test time in minutes. During the nucleation stage, the viscosity has a similar temperature-dependent and time-dependent non-thermal behavior. During the nucleation hold at a constant temperature, the viscosity increases, and the rate of increase depends on the nucleation temperature. During the heating process, the viscosity first decreases and then increases, resulting in sags and local minima. Using the beam bending viscosity (BBV) measurement data of the precursor glass and ceramics and the in situ viscosity measurement data, a unified ceramic viscosity model is established, such as Fig.11 shown. Fig.10 The compositions of the glasses shown are shown in Table 1 below.
[0100] Table 1
[0101] Components weight% <![CDATA[SiO2]]> 73.89 <![CDATA[Al2O3]]> 7.60 <![CDATA[P2O5]]> 2.11 <![CDATA[Li2O]]> 11.50 <![CDATA[Na2O]]> 0.05 <![CDATA[K2O]]> 0.15 <![CDATA[ZrO2]]> 4.24 <![CDATA[SnO2]]> 0.40 <![CDATA[Fe2O3]]> 0.06
[0102] Then, in some embodiments, viscoelastic numerical simulations are performed to understand the effect of these viscosity changes on warpage. Numerical modeling finds that local minimum viscosity combined with in-plane temperature gradients generated during temperature increase can trigger viscous buckling and cause warpage. Figures 12A-12C The warpage for three hypothetical cycles (A, B, C) is shown. Cycle A is the base case; cycle B has a faster viscosity increase rate during nucleation and a higher minimum viscosity during temperature rise; cycle C has a slower viscosity increase rate during nucleation and a lower minimum viscosity during temperature rise. The warpage values for these cases are: C>A>B (at Fig. 12C , Fig. 12A and Fig. 12B ). A lower minimum viscosity will produce a larger viscous buckling type warpage. In other words, increasing the minimum viscosity is beneficial to reducing the buckling type warpage.
[0103] In some embodiments, the minimum viscosity can be maintained at a logarithmic viscosity of greater than or equal to 11.0 poise for any and / or all ramp and hold portions of the heating cycle. For example, the minimum viscosity can be maintained at a logarithmic viscosity of greater than or equal to 11.0 poise for the ramp to the first heating ramp stage, the second heating ramp stage, or the entire thermal treatment cycle. In some embodiments, the minimum viscosity can be maintained at a logarithmic viscosity of greater than or equal to 11.0 poise for any and / or all ramp and hold portions of the heating cycle. In some embodiments, the viscosity of the glass article can be maintained at less than 11.0 poise during at least the nucleation stage, which can be advantageous when 3D forming the glass article during thermal treatment.
[0104] Figures 13A-13C The warpage for three ceramization cycles corresponding to nucleation and growth temperatures of ±10°C is shown. Cycle A was performed at a nucleation temperature of 560°C for 4 hours and a growth temperature of 730°C for 1 hour (see Figure 2). Fig.13A As shown), cycle D has a nucleation temperature of 570 °C for 4 hours and a growth temperature of 740 °C for 1 hour (as shown in Figure 13B), and cycle E has a nucleation temperature of 580 °C for 4 hours and a growth temperature of 750 °C for 1 hour (as Fig. 13C shown). The warpage values in these cases are: E < D < A. Once again, the same trend is shown, that is, increasing the minimum viscosity will reduce the buckling-type warpage. In cycle E, the minimum viscosity remains above 11.0 poise of the logarithmic viscosity during the heating process, and the resulting warpage is very small, for example, < 1 μm.
[0105] When the goal is to ceramize flat glass with minimal warpage, in some embodiments, cycle E is more preferable than other cycles because the minimum viscosity value is lower during the growth heating period. Note that during the nucleation stage, the lower viscosity of cycle E is less likely to cause warpage because ΔT is lower during the temperature holding period (compared to the temperature rising period).
[0106] More generally, in some embodiments, in order to minimize the warpage related to buckling, cycles that produce a higher "minimum viscosity" during the "heating to growth" stage (when the highest ΔT is observed) may be preferred. This can be referred to as the "minimum viscosity" during the heating stage, and this model can be used as a screening tool to predict the impact of this minimum value on the final warpage.
[0107] In addition to increasing the local minimum viscosity to reduce the buckling-type warpage, some weight constraints can also be applied to increase the buckling threshold. In a stacked structure, making the weight on the top of the stack sufficient to prevent the top glass from buckling will ensure that the underlying layers will not buckle either. Applying weight constraints to the top of the stack can also reduce the minimum acceptable viscosity to prevent the glass product from buckling.
[0108] When the component is placed horizontally on the locator material, if the locator is not flat, in addition to warpage caused by viscous buckling, gravity will also cause warpage. The viscous sag analysis is shown in Fig.14 . In a region with a diameter of 30 mm, at a logarithmic viscosity of 11.0 poise and for 0.5 hours, the viscous sag will reach approximately 100 μm. Fig.14 It is shown that a larger area (diameter > 30 mm) / lower viscosity (logarithmic viscosity < 11 poise) / longer duration (> 0.5 hours) will result in a viscous sag of > 100 μm. If the flatness of the locator is better than 100 μm, then under these conditions, the glass will sag and conform to the locator. If the flatness of the locator is greater than 100 μm, then the viscous sag will also be greater than 100 μm. Therefore, in order to minimize the warpage caused by gravity, the locator needs to be flat (for example, less than or equal to 100 microns).
[0109] When the purpose is to form the glass into a 3D shape, in some embodiments, it will be preferred to use a cycle with lower viscosity, and the application of the forming pressure will be consistent with the time period of low viscosity during the cycle. 3D forming can be performed before nucleation, during nucleation, during the temperature rise from nucleation to growth, and in some cases even during the growth holding stage. The appropriate selection may depend on various factors, such as the 3D geometry to be formed, the viscosity of each stage (depending on temperature, time and heating rate) and the warping. For example, since 3D formed glass is ceramicized and can cause significant warping, forming pre-nucleated glass may be a means to reduce the final ceramicization post-warping of the 3D product.
[0110] When 3D forming is to be performed during the nucleation hold, in some embodiments, cycle E (described above with reference to FIG. 13 ) may be preferred over cycles A and D because the viscosity is lower than the other cycles for approximately 100 minutes from the start of the nucleation hold. Fig.14 The results show that for curve E, the viscosity is low enough to cause a few millimeters of sag under gravity within 60 minutes. Therefore, many 3D shapes can be formed under these conditions with the help of additional forming pressure during the nucleation hold stage. In the case of single-mold forming, this pressure can be in the form of a partial or full vacuum on one side of the mold, or a positive gas pressure (usually N2 or air) on the other side of the forming mold. In the case of double (or more) molding, pressure is applied from both sides.
[0111] Alternatively, in some embodiments, 3D forming can be completed entirely in the nucleation to growth ramp phase. In this case, in some embodiments, cycle A will be preferred over cycles D and E. In this case, the buckling risk can still be controlled due to the restraining force of the mold contact / forming pressure.
[0112] It is also possible to consider adopting new cycles during the nucleation process for forming. For example, the nucleation temperature can be further increased in the first part of the cycle, such as to 590°C, 600°C or even 610°C, maintained for a sufficient time to just complete the 3D forming, and then the nucleation temperature can be reduced for the remainder of the cycle (and the duration of the nucleation hold can be shortened if necessary) so that the final crystal content at the end of the cycle is the same as the basic cycle A. Higher temperatures initially produce lower viscosities and allow more challenging shapes to be formed in a shorter time. Having the same crystal content as the base case would mean that in addition to having a favorable phase distribution, the low viscosity of curve A during the temperature increase to growth can be replicated, providing another opportunity to complete 3D forming.
[0113] 3D forming and ceramicization can be performed in the same cycle or in multiple cycles. For example, in one embodiment, the precursor glass can be formed into a 3D shape, and then a separate cycle can be used to ceramicize the 3D product. In another embodiment, the glass preform can be partially or completely "pre-nucleated" in the first cycle, then 3D formed in the second cycle, and then ceramicization can be completed in the second cycle or in a third separate cycle. Since 3D forming of only one glass product can be completed at a time, pre-nucleating the glass preform can increase production by allowing the stacked structure to nucleate compared to nucleating and 3D forming in the same cycle.
[0114] When the glass preform is fully pre-nucleated, the temperature ramp to the growth temperature is a natural choice for 3D forming. As previously described, in some embodiments, cycle A may be preferred over cycles D or E in this case because of the lower viscosity during the ramp to the growth temperature. When the glass is only partially pre-nucleated, 3D forming can be performed during nucleation, during ramp to the growth temperature, or partly during nucleation and partly during ramp to the growth temperature.
[0115] To prevent the 3D article from warping during the ceramicization cycle, ceramicization can be performed on a mold (one-piece, two-piece, or three-piece), the temperature gradient should be kept low (for example, using a mold made of a high thermal conductivity material such as graphite or SiC), and a load should be applied to force the 3D article to remain in contact with the mold during the ceramicization process.
[0116] As described above, precise control of the glass article temperature is required to achieve the desired glass-ceramic article. Therefore, according to some embodiments, thermal uniformity within a heating device (e.g., an annealing furnace or a heating furnace) and within a glass stack is an important attribute of the process. For example, in some embodiments, the variation in temperature provided to the stack is less than or equal to ±8°C, such as less than or equal to ±7°C, less than or equal to ±6°C, less than or equal to ±5°C, or less than or equal to ±4°C, where the temperature is measured on the glass sheet itself.
[0117] In order to achieve the above-mentioned thermal uniformity, thermal mapping is performed on the internal chamber of the empty heating device before the fixture (such as brackets, positioners and glass stacks) are inserted into the heating device. Thermal mapping of the empty heating device chamber is performed to determine the space in which thermal uniformity can be maintained within the required tolerance, thereby determining the available heating space within the heating device chamber. For example, the portion of the heating device chamber that cannot maintain a thermal uniformity that is less than or equal to ±8°C from the programmed cycle temperature will be excluded from the heating space in which the glass stack can be placed. After mapping the empty heating device chamber to determine the available heating space, the fixture is placed in the currently determined heating space and the thermal uniformity of the glass stack is measured to determine whether the glass sheets in a given glass stack can be maintained within the required temperature tolerance of the programmed cycle temperature. Once the thermal uniformity is determined, the glass stack can be configured and placed in the heating space using the thermal uniformity measurement results obtained.
[0118] Now refer to Fig.15A and Fig. 15B A method for determining thermal uniformity within an interior chamber of a heating device is described. In some embodiments, the placement of a measuring device (e.g., a thermocouple) within a chamber of the heating device should take into account the design of the heating device, such as walls, doors, heating elements, vents, etc. of the chamber of the heating device. The measuring device should be placed away from design elements so that any thermal non-uniformity caused by such design elements is reduced during thermal mapping. In addition, the measuring device should be placed in the chamber of the heating device so that the thermal uniformity of the entire heating space can be determined. For example, the measuring device should be placed in the chamber of the heating device so that measurements are performed at multiple locations within the chamber of the heating device to minimize "dead spots" or locations where no measurements are made.
[0119] Fig.15A and Fig. 15B The horizontal and vertical arrangements of the measuring device in the chamber of the heating device are shown respectively. First, considering the design elements of the chamber of the heating device, the expected heating space 310 (consisting of Fig.15A and Fig. 15B The space within the dotted line in the figure is used for estimation. Fig.15A and Fig. 15B As shown, the desired heating volume 310 is selected so that there is space between the top wall, bottom wall and side walls of the heating device chamber. Fig.15A Horizontal arrangements of the measuring devices according to some embodiments are shown (ie, viewed from the top or bottom of the heating device chamber). Fig.15A As shown, fifteen measuring devices (elements 1-15) are placed in a spaced arrangement in each horizontal cross section of the heating device chamber. Fig.15AIn the illustrated embodiment, the measurement devices 1-15 are placed horizontally in the heating device chamber, which will hopefully provide adequate thermal mapping of the horizontal space in the heating device chamber. However, it will be appreciated that other horizontal arrangements of the measurement devices may be used in alternative embodiments.
[0120] Similarly, Fig. 15B The vertical arrangement of the measuring device in the chamber of the heating device is shown (i.e. a side view). Fig. 15B The three rows of measuring devices, top, middle and bottom, are indicated by "T", "M" and "B" respectively, and are placed in a spaced configuration in the heating device chamber. Fig. 15B In the illustrated embodiment, the measurement devices are placed vertically in the upper, middle and lower rows of the heating device chamber, which will hopefully provide sufficient thermal mapping for the vertical space of the heating device chamber. However, it should be understood that other horizontal arrangements of the measurement devices may be used in alternative embodiments. When viewed together, Fig.15A and Fig. 15B Forty-five measuring devices are shown in a spaced configuration (top, middle, and bottom rows of 15 measuring devices each), which will hopefully adequately map the desired thermal performance of the heating space 310. However, it should be understood that other arrangements of measuring devices may be used in alternative embodiments.
[0121] In some embodiments, the measuring devices are arranged as little as possible in every corner, all center lines, and all spatial center points within the expected heating space. If there are thermally non-uniform design elements, additional measuring devices can be placed near such elements to measure the impact of these elements on thermal uniformity and determine how close the heating space may be to these thermally non-uniform design elements. The vertical arrangement of the measuring devices should take into account and in some embodiments will determine the height at which the glass stack and / or fixture can be placed in the heating device chamber. If the top or bottom surface of the heating device chamber is heated or not heated, the adjacent measuring devices should take into account the position of the heater element, as well as any other non-flat surfaces that may disrupt or interrupt the thermal response of the measuring device. In one or more embodiments, the vertical spacing of the heating device empty chamber is every 25 mm from the bottom 320 of the heating device chamber to a distance between 50 mm and 100 mm from the top 330 of the heating device chamber.
[0122] Once the measuring device is placed in the empty chamber of the heating device, a heating cycle is performed. According to some embodiments, the heating cycle may include the same heating conditions as the cycle used for the ceramicization of glass products. During this heating cycle, the measuring device periodically or continuously measures the temperature of their respective positions in the heating device chamber. Then, these temperatures measured by the measuring device can be analyzed and compared to determine whether one or more positions in the heating device chamber are not within the tolerances desired by the programming cycle temperature, such as ± 8 ° C. If one or more positions of the heating device chamber do not fall within the desired tolerances, those positions of the heating device chamber are excluded from the heating space that can be used in the ceramicization cycle. In some embodiments, if one or more positions of the heating device chamber do not fall within the desired tolerances, the movable measuring device can exclude the position that does not fall within the desired tolerances in the heating device chamber, and run one or more other heating cycles, thereby performing additional thermal mapping. This process can be repeated any number of times to determine the heating space that can be maintained within the desired tolerances in the heating device chamber.
[0123] Once the measuring device is in a position such that all measurement positions of the heating device chamber fall within the desired tolerances, the space within the heating device chamber determined by the measuring device will be considered the heating space. In some embodiments, once the heating space is determined, the glass stack and fixtures (e.g., brackets) can be designed and / or configured so that they fit within the heating space. The designed glass stack and fixture are then loaded into the heating space within the heating device chamber, and the measuring device located in the center of the heating space is removed to accommodate the fixture. A heating cycle is performed to determine the effect of the fixture on the thermal uniformity within the heating space, and in some embodiments, the heating cycle is the same as the heating cycle used to determine the heating space. The programmed thermal distribution can then be adjusted to accommodate the effects of the fixture and glass stack.
[0124] According to some embodiments, after determining the effects of the heating space within the chamber of the heating apparatus and the glass stack and fixtures on the thermal response, a measuring device may be placed into the glass stack and any measuring devices used in the previous steps to determine the effects of the heating space and the glass stack and fixtures on the thermal responsiveness may be removed, thereby finding the thermal uniformity within the glass stack.
[0125] According to some embodiments, the placement of the measurement devices within the glass stack is important to provide reliable and repeatable data. The thermal conductivity of the glass should be considered for each layer, so only one piece of glass between the positioner and the measurement device will provide adequate thermal characterization of the glass sheet and will capture the thermal impact of the positioner on the stack. Therefore, in some embodiments, the number of measurement devices included in the glass stack will vary depending on the physical size of the glass stack and the thermal mapping details required. For example, in one or more embodiments, nine measurement devices can be placed in the stack, with three measurement devices placed along the centerline of the glass sheet below the top positioner; three measurement devices placed along the centerline of the glass sheet located at the geometric center of the glass stack; and three measurement devices placed along the centerline of the glass sheet above the bottom positioner. As used in this example, the centerline is a line drawn along the length of the glass sheet that is substantially parallel to two edges of the glass sheet, substantially perpendicular to the other two edges of the glass sheet, and intersects the geometric center of the glass sheet. It should be understood that as used herein, "substantially parallel" and "substantially perpendicular" mean that the centerline is parallel to or perpendicular to such edges, respectively, taking into account edge irregularities caused by manufacturing. In the above-described embodiment where three measuring devices are placed along the centerline of the glass sheet, one measuring device (e.g., a thermocouple) is placed on the centerline near the left side of the glass sheet, one measuring device is placed at the geometric center of the glass sheet, and one measuring device is placed along the centerline of the glass sheet near the right side of the glass sheet. This configuration is followed for all three glass sheets considered. The middle layer of the stack typically provides an intermediate reference for the entire stack. It should be understood that the arrangement of the measuring devices disclosed above is merely exemplary, and other arrangements may be employed in some embodiments depending on the desired specificity of the desired thermal mapping. For example, in an embodiment where thermal uniformity is to be strictly controlled, more measuring devices will be placed on each glass sheet to obtain a more detailed thermal mapping. Any number of measuring devices may be used in the glass stack, as long as the number of measuring devices does not substantially interfere with the thermal distribution of the glass sheets. All layers to be measured can then be measured to understand the response of the thermal distribution of the glass to the programmed thermal distribution, as discussed in more detail below.
[0126] Fig.16 The temperature differences (ΔT) of the stacked glass between the top (i.e., the glass sheet below the top retainer), the middle (i.e., the glass sheet at the geometric center of the glass stack), and the bottom (i.e., the glass sheet above the bottom retainer) of the glass stack are shown, as measured by a measurement device located at or near the geometric center of each glass sheet. Such a graph can be used to understand the magnitude and location of temperature deviations. Fig.16 The temperature of a glass stack having 18 glass sheets and three positioners interspersed within the stack such that there are six glass sheets between every two positioners is shown. Fig.16As shown, the temperature of the glass sheet near the bottom of the glass stack is lower than the temperature of the glass sheet near the middle of the glass stack and the glass sheet near the top of the glass stack. This determination is indispensable because the time and temperature of ceramicizing the ceramic product may affect the change of the expected properties (such as color, haze, stress, phase ensemble, etc.) measured after ceramicization. Therefore, understanding and controlling the temperature difference between the glass sheets in the glass stack has an impact on the final performance of the glass ceramic product.
[0127] In some embodiments, the temperature difference with the expected thermal curvature distribution is measured and analyzed in both the vertical plane and the horizontal plane. The vertical ΔT is usually affected by the selection of the positioner material, the height of the glass stack and the heating and cooling rates of the process equipment. The horizontal ΔT is usually affected by the non-uniformity of the process equipment, the arrangement of the glass stack in the heating space and the heating design (how the heat is directed to the glass stack). According to some embodiments, it is important to control the ΔT in the stack to obtain the uniformity of high-yield glass sheets. It should be understood that the tolerance of ΔT will vary according to the glass composition and the desired properties of the final glass-ceramic product.
[0128] In embodiments where the glass articles have glass compositions disclosed and described herein, during the isothermal holding (also referred to as "holding") phase of the ceramization process (i.e., the phase corresponding to the nucleation phase and the growth phase), the ΔT within the glass stack can be maintained within ±5°C of the programmed temperature profile. When the ΔT exceeds this tolerance range during the isothermal holding of the nucleation and growth phases, the various glass-ceramic sheets from the resulting ceramization process may have undesirable properties, such as warpage, bowing, haze, etc. Fig.17 Results for a glass stack comprising eighteen measurement devices are shown. Fig.17 In FIG. 1 , the x-axis is time measured in seconds, the right y-axis is ΔT in ° C, and the left y-axis is the temperature of the glass piece in ° C. The tight grouping of the plotted lines represents the temperature of the glass piece (corresponding to the left y-axis), while the wider grouping of the plotted lines shows the ΔT of the glass piece (corresponding to the right y-axis). Fig.17 As shown, during the first ramp cycle of heating the glass stack from ambient temperature to about 570° C., ΔT (measured relative to the programmed ceramization temperature) exceeded 40° C. for some glass sheets in the glass stack. However, after the ramp cycle was completed and the isothermal hold began, the ΔT of the glass sheets decreased and remained at or below ±5° C. during the isothermal hold. In some embodiments, the ceramization cycle is adjusted based on the ΔT measurements obtained.
[0129] For example, in one or more embodiments, it is desirable that the duration of the programmed isothermal hold occurs when ΔT is within ±5°C. Fig.17As shown, the constant temperature holding at about 570°C is started before the ΔT of the glass stack is within ±5°C of the programmed ceramicization cycle. Therefore, the programmed isothermal holding can be extended so that the initial duration of the isothermal holding is carried out when the ΔT is within ±°C. As a non-limiting example, if the isothermal holding of about 570°C is initially programmed to have a duration of 4 hours, it may be necessary to keep the glass stack within a range of ±5°C of ΔT for a duration of 4 hours (i.e., matching the initially programmed isothermal holding time). For this reason, the isothermal holding may need to be extended beyond 4 hours to make up for the time it takes for the ΔT of the glass stack to reach the range of ±5°C. The following can be used to Fig.17 The data collected in the manner shown is used to determine how much time to adjust the isothermal hold and determine the time it takes for the ΔT of the entire glass stack to be within ±5° C. In one or more embodiments, the duration of the isothermal hold during the nucleation phase can be adjusted by +10%, for example, +9%, +8%, +7%, +6%, +5%, +4%, +3%, +2%, or +1%.
[0130] Similar to the above description, Fig.17 The ΔT during the ramping cycle from about 570°C to about 750°C is shown to exceed ±5°C, and may exceed 20°C in some glass pieces within the glass stack. However, similar to the isothermal hold at about 570°C during the nucleation phase, the ΔT returns to within ±5°C after a period of isothermal hold at about 750°C during the growth phase. Similar to the isothermal hold at about 570°C, in some embodiments, it may be desirable to maintain the glass stack with a ΔT within ±5°C for the initial programmed duration of the isothermal hold during the growth phase. Thus, the duration of the growth phase isothermal hold may be adjusted as described above so that the glass stack is maintained at a ΔT within ±5°C for the initial programmed duration of the growth phase isothermal hold. In one or more embodiments, the duration of the growth phase isothermal hold may be adjusted by +10%, for example, +9%, +8%, +7%, +6%, +5%, +4%, +3%, +2%, or +1%.
[0131] Fig.18 Detailed view showing the thermal response of a glass stack according to some embodiments. The temperature difference between each glass sheet in the glass stack during various heating and cooling cycles is Fig.18 This information helps understand how the glass stack thermally responds to the programmed heating profile. During the transition process, the deviation of the measured temperature of the glass piece from the programmed heating profile may or may not affect the glass properties, but it may limit the process if the thermal processing equipment is operated at or near 100% power output to achieve the desired heat profile. This data can be used to fine-tune the heat profile to improve or maintain the properties of the final glass-ceramic article.
[0132] The temperature distribution in the heating equipment chamber and in the glass stack provides important information, and in various embodiments, these information can be used to adjust the programming heating distribution used in the ceramicization cycle. In some embodiments, these adjustments to the programming heating distribution will improve the property of the final glass ceramic product, such as warping, bending, haze, transparency, etc. However, in other embodiments, these adjustments to the programming heating cycle may not affect the property of the final glass ceramic product, but can improve the output of the ceramicization process. However, in other embodiments, it may not be necessary to adjust the programming heating cycle based on the measured temperature uniformity. For example, the tolerance requirements of some terminal products are very high, and therefore very transparent flat glass products are required. For such products, it may be necessary to adjust the programming heating cycle. However, other terminal products may have a larger tolerance to the transparency, color, flatness and stress of glass. For such products, it may not be desirable to adjust the programming heating cycle based on the thermal uniformity in the glass stack.
[0133] As discussed in detail above, in some embodiments, in view of the collected thermal uniformity data, it may be desirable to adjust the programming heating cycle. However, the thermal uniformity in the glass stack can also be controlled. As described above, the vertical ΔT can be controlled by changing the stack structure, the locator material, the locator structure (e.g., inserting an intermediate layer made of locator material between the top locator and the bottom locator), etc. Another way to control the thermal uniformity in the glass stack is to use multi-stage heating in the ceramicization cycle. By using multi-stage heating to reduce the heating rate during the nucleation and / or growth stage, the heating of the glass stack will be caused to be slower, therefore, the thermal uniformity of the glass sheet will be increased. An exemplary embodiment of multi-stage heating is disclosed below.
[0134] By setting the heating source (e.g., radiant heater, convection heater, etc.) at multiple intermediate levels during heating, the thermal uniformity of the glass sheet can be improved due to the adjustment of the heating rate. The effectiveness of this multi-stage heating operation can be evaluated using a complete lehr thermal model with a capacity of 9 stacks on a single carrier with 23 glass sheets in each stack. For heating from room temperature to nucleation conditions, a nine-stage heating scheme was investigated, and Table 2 summarizes the heater temperature levels controlled in each stage. Fig.19 It is shown that the temperature variation of the glass sheet is significantly reduced compared to single stage heating with the heater set to a nucleation temperature of 570°C. For multi-stage heating, the heating rate is reduced and a longer heating time is required to reach the target nucleation temperature. For the above nine-stage heating, it takes 180 minutes to reach the nucleation temperature, while the single stage heating takes 100 minutes. Multi-stage heating can be optimized to reduce thermal variation below a favorable level without adding a large amount of heating time.
[0135] Table 2
[0136]
[0137] A multi-stage heater setup can also be used to heat the growth stage and reduce thermal variations on the glass sheet. Fig. 20 The same effect is shown in , which shows that the maximum glass sheet temperature variation is reduced from 40°C to about 25°C with the three-stage heater setting. The actual heater temperatures for the three-stage heating are set to 620°C, 680°C and 740°C, while the heater for the single-stage heating is set to a constant value of 740°C.
[0138] In some embodiments, in order to meet the stress and warpage requirements of the glass ceramic products, it is important to keep the thermal changes low during the cooling process after growth. By controlling the thermal environment to which the hot glass stack dissipates heat, the cooling rate can be controlled, which has the potential to reduce the thermal changes of the glass sheets. In lehr operations, this can be achieved by setting the heater at multiple intermediate levels during the cooling phase. A complete lehr thermal model with mass production capabilities is used to evaluate the effectiveness of multi-stage cooling. Fig.21 As shown, the temperature variation of the glass sheet is significantly reduced compared to single-stage cooling. Multi-stage cooling is carried out in four stages, and the heater is controlled at 665°C, 590°C, 515°C and 440°C respectively. For single-stage cooling, the heater is set to 300°C. A compromise of multi-stage cooling is a lower cooling rate, or it takes longer to reach the target outlet temperature. For the above four-stage cooling, the average cooling rate is 3.3°C, which is lower than 5.3°C in the case of single-stage cooling.
[0139] In view of the above disclosure, the thermal uniformity of the glass stack can be partially controlled by the configuration of the glass stack, the positioner, and the interlayer. In addition, the thermal uniformity of the glass stack can be partially controlled by the heating cycle used to heat the glass stack to the nucleation and growth temperatures. One or more of these controls can be used for ceramicization cycles with smaller tolerances for thermal uniformity, such as when it is desired to control ΔT within ±5°C.
[0140] Fig. 22 Shown is a conventionally obtained ceramicization cycle (labeled as COR), which has two isothermal steps and a linear heating rate compared to the AVC cycle of various target viscosities. As shown in the overlapping nucleation and growth steps, there is no isothermal step in the AVC method, and the temperature increases at a relatively slower rate than the transition step. This also helps to shorten the total ceramicization duration.
[0141] Fig.23 Shown with Fig. 22Evolution of density for the same conventional COR and AVC cycles is shown. As expected, the density remains constant during the nucleation step, so minimal deformation / flow gradients are observed, until the crystal starts to grow. Then, the transition follows a smoother trend, unlike the conventional approach where an unavoidable non-monotonic behavior is observed with an abrupt drop in density.
[0142] It is obvious to those skilled in the art that various improvements and changes can be made to the embodiments described herein without departing from the spirit or scope of the subject matter for protection. Therefore, the specification is intended to cover improvements and changes to the various embodiments described herein, as long as such improvements and changes fall within the scope of the attached claims and their equivalents.
Claims
1. A method for ceramizing a glass article to form a glass-ceramic, comprising: heating the glass article to a first holding temperature at a first predetermined heating rate determined at least in part based on performance of an automated viscosity control system, wherein a logarithm to the base 10 of a viscosity of the glass article in poise is maintained greater than or equal to 11.0 during heating of the glass article to the first holding temperature; maintaining the glass article at a first holding temperature for a first predetermined duration, wherein a viscosity of the glass article is maintained within a range of ±1 unit of the logarithm to the base 10 of a target viscosity in poise during the first predetermined duration; heating the glass article from the first holding temperature to a second holding temperature at a second predetermined heating rate determined at least in part based on the performance of the automatic viscosity control system, wherein a viscosity of the glass article is maintained within a range of ±1.0 units of the base 10 logarithm of a target viscosity in poise during at least a portion of the time the glass article is heated from the first holding temperature to the second holding temperature; The glass article is maintained at a second holding temperature for a second duration, wherein the second duration is determined according to a density change rate of the glass article, and at the end of the second duration, the absolute value of the density change rate is less than or equal to 0.10 (g / cm 3 ) / min.
2. The method according to claim 1, wherein when the absolute value of the density change rate of the glass product is equal to 0.00 (g / cm 3 ) / min, the second duration ends.
3. The method of claim 1, wherein the density of the glass article is monitored in situ during heating the glass article from the first holding temperature to the second holding temperature and holding the glass article at the second holding temperature for the second duration.
4. The method of claim 3, wherein the density of the glass article is monitored in situ using a non-contact dilatometer.
5. The method of claim 1, wherein the second duration ends when the density of the glass article is constant for at least 15 minutes.
6. The method of claim 1, wherein the second duration ends when the density of the glass article is constant for at least 50 minutes.
7. The method of claim 1, further comprising applying a weight restraint to the glass article.
8. The method of claim 1, wherein the temperature of the glass article is within ±8°C of the programmed temperature during the first predetermined duration.
9. The method of claim 1, wherein during the second duration, the temperature of the glass article is within ±8°C of the programmed temperature.
10. The method of claim 1, wherein heating the glass article to the first hold temperature at the first predetermined heating rate comprises multi-stage heating.
11. An apparatus for ceramizing a glass product into a glass ceramic, comprising: a heating furnace for receiving glass products; A three-point beam bending apparatus for calculating the transient viscosity using the deflection rate of the glass beam under constant stress in the three-point beam bending apparatus; as well as Automatic viscosity controller for: receiving data from a linear variable differential controller for collecting furnace temperature and glass product viscosity data; as well as The viscosity of the glass article is controlled and the thermal profile of the glass article is achieved by controlling the temperature of the furnace based on at least the temperature of the furnace and the viscosity of the glass article.
12. The apparatus of claim 11, wherein the automatic viscosity controller is used to maintain the base 10 logarithm of the viscosity of the glass article in poise at greater than or equal to 11.0 during the process of forming the glass-ceramic from the glass article.
13. The apparatus of claim 11, wherein an automatic viscosity controller is used to maintain the temperature difference between the glass article and the heat distribution temperature within ± 8°C.
14. The apparatus of claim 12, wherein an automatic viscosity controller is used to control the viscosity of the glass article using a proportional-integral-derivative control loop.
